Removal of heavy metals from oil refinery effluent by micellar-enhanced ultrafiltration (MEUF) - Fallah Hashemi; Hassan Hashemi; Mansooreh Dehghani; Mohammad Hoseini (Shiraz University of Medical Sciences, 2018)
Introduction: One of the major pollutants in the environment is heavy metals. The stability of heavy metals in the environment has created a lot of problems. Refinery effluents are one of the most important sources of heavy metals and should be treated before being discharged into the environment.    Methods: This interventional experimental study aimed to remove heavy metals from petroleum effluent by using the micellar-enhanced ultrafiltration (MEUF) at Kermanshah Oil Refinery. Since ultrafiltration membranes alone cannot remove the heavy metals, surface active agents, such as surfactants, are injected into the effluent. Surfactant monomers in reaction to metal ions creating a complex that cannot cross the ultrafiltration membrane. Heavy metals are removed from the effluent stream. In the present study, Sodium Dodecyl Sulfate (SDS) as surfactant was used to add the effluent to improve the process of heavy metal removal. Result: The results showed that heavy metals such as nickel, lead, cadmium and chromium decreased by 96%, 95%, 92% and 86%, respectively. In the inlet effluent with increasing pH, the efficiency of the processes for metal removal increased, so that at pH = 10, the highest removal efficiency was observed.   Conclusion: According to the results of this study, the use of membrane processes as a practical and efficient method in industrial wastewater treatment can be applied in various industries, especially refinery ones.